Endovascular Management in a Case of Recurrent Bleed Following Transurethral Resection of the Prostate - R. B. Nerli; Vishal Kadeli; Naveen Mulimani; Shridhar C. Ghagane (The Arab Journal of Interventional Radiology, 2018)
Transurethral resection of prostate (TURP) remains the gold standard surgical therapy for symptomatic benign prostatic enlargement, with reported International Prostate Symptom Score reduction of up to 70%. However, as many as 20% of patients can have significant complications including sexual dysfunction, perioperative bleeding requiring blood transfusion, and incontinence. Intractable hematuria from the prostate can be life-threatening, and its management remains a difficult clinical problem. Prostate artery embolization (PAE) is occasionally indicated in such patients when all other measures have failed. PAE has been used to treat benign prostatic hyperplasia; however, literature related to its use for bleeding following TURP remains limited. We report a case of an elderly male who presented with recurrent episodes of hematuria following TURP and was successfully treated by endovascular management.